Skarn-type ilmenite mineralization of the Tuzbasi-Tunceli region, eastern Turkey - Altunbey, M; Sagiroglu, A (Pergamon-Elsevier Science Ltd, 2003)
In the Tuzbasi-Tunceli region of eastern Turkey, skarn-type ilmenite mineralizations occur within the skarn zones along the contact between marbles of the Keban Metamorphic Formation (Permo-Triassic) and gabbros and diorites of the Elazig Magmatic Complex (Coniacian-Campanian). The Elazig Magmatic Complex has characteristics typical of arc magmatism and is composed of plutonic, volcanic, subvolcanic and pyroclastic rocks. Both formations are overlain by sediments of the Alibonca Formation (Lower Miocene) and continental andesitic lava flows of the Karabakir Formation (Upper Miocene-Pliocene). Ilmenite and skarn formation developed as a consequence of plutons (granite-gabbro-diorite) of the Elazig Magmatic Complex intruding into marbles of the Keban Metamorphic Formation. This event also resulted in different types of magnetite mineralization and skarn formation, with different mineral assemblages, in neighbouring areas. Ilmenite concentrations occur as lensoid bodies in garnet-pyroxene calcic exoskarns along (gabbro-diorite)-marble contacts. Ilmenite bodies form syngenetically with skams, and their TiO2 contents reach up to 15.83 wt%. The predominant ore mineral is ilmenite, which is often altered to leucoxene and hematite, and occurs disseminated within skarn minerals (predominantly almandine garnet and pyroxene). The titanium of ilmenites apparently originated from the diorites and gabbros, which are otherwise Ti and Al-rich and Si-poor. The intruded marbles supplied the necessary O-2 for ilmenite mineralization. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: ilmenite Skarn-type ilmenite; Turkey; ilmenite composition